The comprehensiveness and intersectoral approach of primary health care in the network for addressing violence against women (Revista Contexto & Saúde, 2024)
The objective was to analyze the performance of Primary Health Care in caring for women in situations of domestic and family violence in a municipality in the interior of Northeast Brazil. This is a qualitative exploratory-descriptive research involving seven professionals assigned to Primary Health Care (PHC) and Management. The data collection took place between February and March 2022, through semi-structured interviews and a field diary. The results reveal a weakened, disjointed care network without established flows and protocols, where communication between services is limited to individual referrals. Furthermore, professionals are unfamiliar with the majority of services within this network, hindering the provision of comprehensive, intersectoral, and effective care. However, they identify potential strengths, such as recognizing the strategic and important role of Primary Health Care (APS) as the gateway for women experiencing violence.
Keywords: Violence Against Women; National Health Strategies; Primary Health Care; Intersectoral Collaboration; Health Comprehensiveness